The Influence of Learning Organization, Training and Knowledge to Official’s Work Effectiveness in Regency Government of Ogan Komering Ilir (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to determine the influence of learning organization, training, and knowledge to the official’s work effectiveness. This study used a quantitative approach with survey method and path analysis techniques. The study population was all of echelon IV official in regency government of Ogan Komering ilir. The respondents were 233 out of 560 all echelon IV officials in Regency Government of Ogan Komering Ilir. These research findings were as follows: 1) learning organization has the direct effect to the official’s work effectiveness. 2) Training has the direct effect to the official’s work effectiveness. 3) Knowledge has the direct effect to the official’s work effectiveness. 4) Learning organization has the direct effect to knowledge. 5) Training has the direct effect to knowledge. 6) Learning organization has the direct effect to training. The conclusion of this research was that the improvement of learning organization, training and knowledge will increase the official’s work effectiveness. And the better learning organization and training will increase knowledge. Moreover the improvement of learning organization will give a better training.